2016
DOI: 10.1007/s00248-016-0799-4
|View full text |Cite
|
Sign up to set email alerts
|

Syntrophic Interactions Within a Butane-Oxidizing Bacterial Consortium Isolated from Puguang Gas Field in China

Abstract: Butane oxidation by the hydrocarbon degradation bacteria has long been described, but little is known about the microbial interaction in this process. To investigate this interaction, the efficiency of butane oxidation was estimated in monocultures and co-cultures of six strains of butane-oxidizing bacteria (BOB) and a butanol-oxidizing strain. Results showed that the butane degradation velocity was at least 26 times higher in the co-culture of the seven strains (228.50 nmol h(-1)) than in the six individual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…We also found that bmoX genes were associated with butane degradation in G samples, as the increased abundance of bmoX genes in the G samples ( Figure 4 ) was positively correlated with the significant butane degradation taking place in the G microcosms (Supplementary Table S1 ). Zhang Y. et al (2016) observed a similar phenomenon, i.e., bmoX genes were upregulated as the butane degradation rate increased. High concentrations of oil might be toxic to microbes ( Samanta et al, 2002 ), and therefore, many studies have reported that oil contamination decreases the diversity of microorganisms and the relevant functional genes in a variety of environments ( Liang et al, 2011 ; Bell et al, 2013 ; Yang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…We also found that bmoX genes were associated with butane degradation in G samples, as the increased abundance of bmoX genes in the G samples ( Figure 4 ) was positively correlated with the significant butane degradation taking place in the G microcosms (Supplementary Table S1 ). Zhang Y. et al (2016) observed a similar phenomenon, i.e., bmoX genes were upregulated as the butane degradation rate increased. High concentrations of oil might be toxic to microbes ( Samanta et al, 2002 ), and therefore, many studies have reported that oil contamination decreases the diversity of microorganisms and the relevant functional genes in a variety of environments ( Liang et al, 2011 ; Bell et al, 2013 ; Yang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 58%
“…Gammaproteobacteria species from the genus Pseudomonas is widespread in the natural environment and is able to metabolize a wide range of organic compounds ( Salgado-Brito et al, 2007 ; Dong et al, 2015 ; Baruah et al, 2016 ; Hemidouche et al, 2016 ), including light hydrocarbons ( Zhang Y. et al, 2016 ). For this reason, Pseudomonas was entrusted with the task of biodegrading hydrocarbon pollutants in contaminated sites, as well as serving as a biological indicator of oil and gas reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, we use concentration of microbes after retaining them on the lter paper, therefore, there is a possibility of the presence of helper species which can be a facilitating factor for growth of those microorganisms that have been previously uncultured. Different studies have proven in the past years that the presence of some microorganisms and sometimes a small distance between the two microorganisms like less than 2µm facilitates the growth of microorganisms in co-culture [47][48][49]. We would like to explore these synergistic relationships in future.…”
Section: Discussionmentioning
confidence: 99%